The State of Forest Genetic Diversity: Anthropogenic Impacts and Conservation Initiatives - Konrad, Heino; George, Jan-Peter; Szukala, Aglaia (Springer Nature Switzerland, 2025)
Genetic diversity is a key pillar of biodiversity, underlying the adaptive potential of any species. At the same time, it is difficult to quantify this component of biodiversity, and we know very little about the genetic diversity status of most species. A wealth of studies points toward a substantial decline, which is also apparent in numerous forest species. Connectivity is fundamental to maintaining high levels of genetic diversity and adaptability via gene flow between populations. In this chapter, we attempt to elucidate the importance of genetic diversity for the entire forest ecosystem with a focus on its main components: tree species. We elaborate on the anthropogenic factors impacting forest diversity, like exploitation and artificial regeneration, climate change, and introduced pests. An overview of molecular methods for studying genetic diversity and connectivity is presented. Regular genetic monitoring is imperative for optimizing conservation strategies such as the creation of stepping stones to counteract population fragmentation. We highlight the importance of taking genetic diversity into account when sourcing plant material for forest and landscape restoration projects. Finally, international efforts to conserve genetic diversity are presented along with recommendations on suitable indicators to monitor it. Scientists working on genetic diversity are encouraged to actively participate in national and international processes to incorporate genetic principles into policy development as well as conservation and restoration efforts.
Keywords: climate change; forest genetic resources; forest reproductive material; genetic rescue; human impact